Gerakan Reformasi Gereja di Eropah dan Kesannya Terhadap Pegangan Seksualiti Masyarakat Barat - Abdul Rani, Mohd Zariat (Jurnal Usuluddin, 2001)
Before the 15th century, most of the Europe an community lifestyles were controlled and determined by the doctrines established by the Roman Catholic Church. However, the reformation movements in most of those challenged the doctrines and introduced their own interpretations and views. One of those affected aspects was regarding sexuality. The main arguments of the reformists included the concept of continence, vow of chastity and celibacy practice of the priests of Roman Catholic Churches. Marriage institution which was more inferior compared to the celibacy practice and the ban of divorce practice among the Christians were also being criticized. This article explores this reformation process and study changes that occurred in Westerners understanding and belief towards sexuality.